Thermal decomposition kinetic study of multiwalled carbon nanotube buckypaper-reinforced poly(ether-imide) composites. (January 2019) - Ribeiro, Bruno; Santos, LFP; Santos, AL; Costa, ML; Botelho, EC
Poly(ether-imide) (PEI)-based composites filled with multiwalled carbon nanotubes in a dispersed form (1.0 wt%) and as buckypaper (BP) (25 wt%) have been prepared by mixing solution and hot compression molding technique, respectively. Vacuum filtration technique with the aid of water-based surfactant Triton X-100 was employed to produce BP sheets. The thermal stability of the composites was evaluated by thermogravimetric analysis and revealed a strong increase in thermal degradation temperature when BPs were used as nanofiller. Ozawa–Wall–Flyn model was used to determine the kinetic parameters. It was observed an increase in activation energy as the nanotubes concentration rise, suggesting the formation of more thermally stable systems. In addition, half-life time as function of temperature demonstrated that BP-based composites could operate for 3200 years at 200°C. These results concluded that carbon nanotube BP could contribute to improve significantly the thermal stability of PEI matrix.